2008
DOI: 10.1177/1466424008092798
|View full text |Cite
|
Sign up to set email alerts
|

Improved arthritic knee health in a pilot RCT of phytotherapy

Abstract: Although practitioner-prescribed 'western' herbal medicine (phytotherapy) is a popular complementary therapy in the UK, no clinical studies have been reported on patient-orientated outcomes. The objective of this pilot study was to investigate the effects of phytotherapy on symptoms of osteoarthritis of the knee. A previous study of Chinese herbal medicine for the treatment of irritable bowel syndrome, published in the Journal of the American Medical Association, acted as a model in the development of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…From the retrieved 122 references, 115 were discarded for the following reasons: Reviews or outreach papers like editorials, letters etc (72), in vitro studies 5, animal studies (8), not concerning OA (9), no placebo or not a controlled study (6), and finally not concerning oral ginger intake (15). Seven references were read in full-text, and two of those were discarded; one due to no oral ginger intake 39 , and one due to no placebo 40 . Five studies were finally included in the meta-analysis 41e45 .…”
Section: Discussionmentioning
confidence: 99%
“…From the retrieved 122 references, 115 were discarded for the following reasons: Reviews or outreach papers like editorials, letters etc (72), in vitro studies 5, animal studies (8), not concerning OA (9), no placebo or not a controlled study (6), and finally not concerning oral ginger intake (15). Seven references were read in full-text, and two of those were discarded; one due to no oral ginger intake 39 , and one due to no placebo 40 . Five studies were finally included in the meta-analysis 41e45 .…”
Section: Discussionmentioning
confidence: 99%
“…Standardized preparation of C3 curcuminoids (curcumin, demethoxycurcumin, and bisdemethoxycurcumin) 600 mg/day (Kositchaiwat et al, 1993) Capsules (250 mg each) containing Curcuma longa powder NR 250 mg/day (Hamblin et al, 2008) Tincture 1:5 from Curcuma longa NR 930 mg/day (Satoskar and Shenoy, 1986) Capsules containing curcumin…”
Section: Curcuma Longa Lmentioning
confidence: 99%
“…Reasons for excluding studies were: (a) not a randomised controlled trial (Grahame 1981; Guyader 1984; Kagore 2011; Linsheng 1997; Loew 1996;Mishra and Singh 2003;Myers 2010; Saley 1987; Srivastava 1989; Wang 1985; Wegener 2003; Xu 2005; Yuelong 2011; Zell 1993), (b) review or discussion paper (Anonymous 1993; Brien 2006; Chrubasik 1998; Dharmananda 1985; Falch 1997; Gendo 1997; Kielczynski 1997; Long 2001; Reuss 1981), (c) not a herbal intervention (Belcaro 2010; Levy 2009; Park 2009), (d) unable to identify the herbal components of the intervention (Jacquet 2009; Kulkarni 1991), (e) individualised treatments thus not a standardised herbal intervention (Fang 2008; Hamblin 2008), (f) mixed sample and unable to extract data for participants with OA only (Biswas 1998;Du 2006; Lechner 2011; Schaffner 1997), (g) duplicate publication or part thereof (Chantre 2000; Lung 2004; Rein 2004b; Schmid 2001; Winther 2004), (h) abstract publication only (Biswas 1997; Schmid 1998a), or (i) did not include functional or clinical outcomes (Zeng 2008). Sub-analyses of two studies (Jung 2004; Rein 2004a) were identified in other publications (Lung 2004; Rein 2004b; Winther 2004) and were excluded from this review to avoid repetition of data.…”
Section: Resultsmentioning
confidence: 99%